Characteristics of glucose-6-phosphate dehydrogenase mutations in newborns with deficiency from 2021 to 2022 in the Heze area of China - Zhang, Xin; Duan, Yanan; Zhang, Xiao; Li, Miaomiao; Li, Ling; Zhang, Renwei; Liu, Shiguo (Frontiers in Immunology, 2025)
IntroductionGlucose-6-phosphate dehydrogenase (G6PD) deficiency has a distinct regional and ethnic heterogeneity in distribution, and information on the molecular characteristics of G6PD deficiencies in the Heze area, Shandong Province, China, is limited. We aimed to explore the incidence and genetic mutations characteristic of G6PD enzyme deficiencies in newborns in the Heze area to investigate the pathogenicity of new G6PD mutations.MethodsWe measured G6PD activity in 114,285 neonates born in the Heze area and identified 80 patients with G6PD deficiencies. The genetic mutations in G6PD in these patients were analyzed using Sanger sequencing. Functional studies were conducted by constructing eukaryotic expression vectors, transfecting them into HEK-293T and HELA cells, and measuring the mRNA and protein levels and G6PD enzymatic activity.ResultsThe incidence of G6PD deficiency in the study population was 0.07% (80/114,285). We identified 17 mutation types with a 100% G6PD mutation detection rate, with four of them being significant: c.479G>A, c.404A>T, and c.486-7C>G being globally novel mutations, while c.682G>A has never been reported in China before. Functional studies revealed that the heterozygous missense mutations c.479G>A/p.S160N and c.404A>T/p.N135I increased mRNA levels, decreased protein expression, and reduced G6PD activity.DiscussionThe incidence of neonatal G6PD deficiency in the Heze area is low, and the most commonly mutated loci were c.1388G>A, c.487G>A, and c.1376G>T. Among these mutations, c.479G>A/p.S160N, and c.404A>T/p.N135I are potentially pathogenic. These mutations may cause G6PD deficiency via different mechanisms, thereby requiring further experimental investigation.